Prescription-related risk factors for opioid-related overdoses in the era of fentanyl contamination of illicit drug supply: A retrospective case-control study. Issue 1 (1st December 2022) - Smolina, Kate; Crabtree, Alexis; Chong, Mei; Park, Mina; Mill, Christopher; Zhao, Bin; Schütz, Christian G.
Abstract: Background: We sought to quantify the association between clinical, physiological, and contextual factors and opioid-related overdose, specifically focusing on current and past use of select prescription medications. Methods: We conducted a case-control study of individuals who experienced a non-fatal opioid-related overdose between January 2015 and November 2016 in British Columbia, Canada. We matched 8, 831 cases to 44, 155 controls on birth year, sex, and local health area of residence and examined 5-year prescribing history for opioids for pain, medications for opioid use disorder (MOUD), benzodiazepines/z-drugs, and other psychoactive medications. Results: The overall prevalence of prescription opioid drug use was generally low in the study population. Cases had a relatively higher use of selected prescription medications, a higher physical and mental morbidity burden, and were less connected to health services compared with controls. For opioids for pain, current therapy was associated with experiencing an overdose (OR = 8.5, 95%CI: 7.3–10); history of long-term use had a stronger association than history of short-term use (OR = 2.9, 95%CI: 2.6–3.3 vs OR = 1.7, 95%CI: 1.5–1.8, respectively). While persons on MOUD were more likely to overdose compared to persons who were not on therapy (OR = 2.0, 95%CI 1.7–2.4), recent discontinuation of MOUD greatly increased the likelihood of overdose (OR = 25.6, 95%CI 17.5–37.4). Active therapy of benzodiazepines/z-drugs and other sedating medications also significantly increased the likelihood of overdose. Conclusions: While this study supports expansion of efforts to prevent overdoses among individuals actively using opioids for pain and improve retention among those on MOUD, it is also important to address other clinical, physiological, and contextual risk and protective factors to help curb the current overdose crisis.